2021
DOI: 10.1136/bmjopen-2020-047680
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of COVID-19 on the quality of life of the survivors, partners and family members: a cross-sectional international online survey

Abstract: ObjectiveThis study aimed to measure the impact of COVID-19 on the quality of life (QoL) of survivors and their partners and family members.Design and settingA prospective cross-sectional global online survey using social media.ParticipantsPatients with COVID-19 and partners or family members (age ≥18 years).InterventionOnline survey from June to August 2020.Main outcome measureThe EuroQol group five dimensions three level (EQ-5D-3L) to measure the QoL of survivors of COVID-19, and the Family Reported Outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 25 publications
8
63
1
Order By: Relevance
“…First, questionnaires can only be distributed to users who have registered on the platform. So the online survey may lead to selection bias, limiting the generalizability of our findings [ 42 ]. Second, there may be more factors that can affect the results, such as people’s social network, their participation in online health communities, and other social and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…First, questionnaires can only be distributed to users who have registered on the platform. So the online survey may lead to selection bias, limiting the generalizability of our findings [ 42 ]. Second, there may be more factors that can affect the results, such as people’s social network, their participation in online health communities, and other social and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a decrease in HRQoL across multiple domains with lower scores in patients recovering from severe COVID-19. 4,5,10,14,15,17,18,28 Simultaneously to persistent symptoms and decreased HRQoL, some studies have also reported residual chest imaging abnormalities and lung diffusion impairment up to 6 months after recovery from acute illness, suggesting one possible explanation for long COVID syndrome. 5,15 To further understand the long-term effect of COVID-19 disease as compared to other respiratory illnesses, we matched a subgroup of our study patients to patients that were hospitalized with non-COVID-19 pneumonia during the same period.…”
Section: Discussionmentioning
confidence: 99%
“…14 In additional studies, healthrelated quality of life (HRQoL) was decreased in the weeks following recovery from acute COVID-19 infection, including decreased mobility and physical functioning, decreased social functioning, anxiety, depression, and pain. [4][5][6][7][15][16][17][18] Other pathogens causing pneumonia and hospitalization can adversely affect PROMs and cause a decrease in HRQoL during the months following discharge. This has been previously shown in patients recovering from community-acquired pneumonia even up to 1 year after infection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the follow-up of these patients could be furtherly complicated by the health systems overload due to the repeated pandemic waves and by the need to recover ordinary activity for non-COVID diseases [22]. A recent online survey evidenced both physical and mental sequelae one year after COVID-19 syndrome for both survivors and their relatives, with age, sex, distance from COVID-19 diagnosis, and length of hospital stay being significant predictors of HRQoL impairment [23]. This is the first literature report specifically focusing on ICU survivors who required IMV and our results strengthen the information that more than half of C-ARDS survivors report significant impairment in HRQoL and persistent symptoms, in particular dyspnea, at 1 year after ICU discharge.…”
Section: Health-related Quality Of Life Trajectoriesmentioning
confidence: 99%